2019
DOI: 10.3329/bpj.v22i1.40082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Values and Phytochemical Properties of Devil’s Cotton (Ulatkambal) - A Review

Abstract: Devil’s cotton (Ulatkambal) is a genus in the family Malvaceae, with one or two species from Asia and Australia. Literature review revealed that Abroma augusta (Devil’s cotton) is widely used in Ayurvedic medicine as a popular drug. Devil’s cotton has been claimed to possess major biological activities like anti-diabetic, analgesic, anti-inflamatory, thrombolytic, antioxidant, hypolipidemic etc. They are also utilized by the traditional local healers of different Asian countries to treat various diseases like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This makes it valuable in treating conditions like amenorrhea, dysmenorrhea, and other menstrual disorders. [15] While there is no existing research on the plant's anti-ulcer effects, this study aimed to establish the pharmacological foundation supporting its traditional use in treating gastric ulcers. Based on this, an attempt has been made to investigate the protective action of roots of A. augusta in gastric ulcer prevention induced by ethanol in rats with their phytoconstituents.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%
“…This makes it valuable in treating conditions like amenorrhea, dysmenorrhea, and other menstrual disorders. [15] While there is no existing research on the plant's anti-ulcer effects, this study aimed to establish the pharmacological foundation supporting its traditional use in treating gastric ulcers. Based on this, an attempt has been made to investigate the protective action of roots of A. augusta in gastric ulcer prevention induced by ethanol in rats with their phytoconstituents.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%
“…augusta (L.) (family: Sterculiaceae or Malvaceae in some classifications) is commonly known as Ulatkambal in Bengali and Hindi, and Devil's cotton in English. It is an evergreen small shrub with a long history of medicinal uses and mostly found in tropical Asia, South Eastern Africa, and Australia [15]. In India, the mother tincture of A. augusta is widely used in homeopathic medicine to treat uterine disorders and diabetes mellitus [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…http://journal.uinsgd.ac.id/index.php/biodjati Khasanah & Kusumarini 2020; Chowdhury et al, 2019). Many studies have reported about biological activities of this plant such as anti-diabetic (Ahmad et al, 2020;Khanra et al, 2015), anti-inflammatory (Das et al, 2012;Latief et al, 2020), analgesic, antioxidant, thrombolytic, and hypolipidemic activities (Chowdhury et al, 2019). According to Saikot et al (2012), the acetone extract of its leaves also has antimicrobial and cytotoxic activity.…”
mentioning
confidence: 99%
“…Some phytochemicals, such as steroids, triterpenes, flavonoids, alkaloids, abromines, sterols, friedelin, abromasterol, taroxerylacetate, taraxerol, β-sitosterol, etc. are related to its biological activities and found and distributed in almost all body parts of the plant (Chowdhury et al, 2019;Gupta et al, 2011). Hence, the barks, leaves, and roots of A. augusta L. can be used in disease/ disorder treatment (Chowdhury et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation